Formation of nanostructure and mechanical properties of titanium with different purity - Kislyak, I.F.; Kutniy, K.V.; Okovit, V.S.; Tikhonovsky, M.A.; Khaimovich, P.A.; Kolodiy, I.V.; Kalchenko, A.S. (Вопросы атомной науки и техники, 2018)
The effect of quasi-hydrostatic extrusion at liquid nitrogen temperature and room temperature on the evolution of
structure and mechanical properties of iodide titanium and technically pure titanium VT1-0 obtained by severe plastic deformation under the scheme of upsetting-extrusion-drawing (iodide titanium) and screw extrusion-drawing (titanium VT1-0) has been examined. It was shown that combination of severe plastic deformation with cryogenic
quasi-hydrostatic extrusion allowed to create nanocrystalline titanium of various purity with high strength and plasticity. It is established that, at approximately the same grain sizes, the strength characteristics of technically pure
nanotitanium are significantly higher, and the plastic properties are lower than those of iodide nanotitanium. Досліджено вплив квазігідроекструзії при азотній і кімнатній температурах на еволюцію структури та
механічні властивості йодідного титану і технічно чистого титану марки ВТ1-0, отриманих за допомогою інтенсивної пластичної деформації за схемами осаджування–видавлювання–волочіння (йодідний титан) і гвинтова екструзія–волочіння (титан марки ВТ1-0). Показано, що поєднання інтенсивної пластичної деформації
та кріогенної квазігідроекструзії дозволило створити нанокристалічний титан різної чистоти з високими
значеннями міцності і пластичності. Встановлено, що при приблизно однакових розмірах зерен міцностні
властивості технічно чистого нанотитану істотно вищі, а пластичні нижчі, ніж в йодідного нанотитану. Исследовано влияние квазигидроэкструзии при азотной и комнатной температурах на эволюцию структуры и механические свойства йодидного титана и технически чистого титана марки ВТ1-0, полученных с
помощью интенсивной пластической деформации по схемам осадка–выдавливание–волочение (йодидный
титан) и винтовая экструзия–волочение (титан марки ВТ1-0). Показано, что сочетание интенсивной пластической деформации с криогенной квазигидроэкструзией позволило создать нанокристаллический титан различной чистоты c высокими значениями прочности и пластичности. Установлено, что при приблизительно
одинаковых размерах зерен прочностные характеристики технически чистого нанотитана существенно выше, а пластические ниже, чем у йодидного нанотитана.